The Interaction of Diabetes and Tuberculosis: Translating Research to Policy and Practice - Reinout van Crevel; Julia A. Critchley (Tropical Medicine and Infectious Disease, 2021)
Diabetes Mellitus increases the risk of developing Tuberculosis (TB) disease by about three times; it also doubles the risk of death during TB treatment and other poor TB treatment outcomes. Diabetes may increase the risk of latent infection with Mycobacterium tuberculosis (LTBI), but the magnitude of this effect is less clear. Whilst this syndemic has received considerable attention, most of the published research has focussed on screening for undiagnosed diabetes in TB patients or observational follow-up of TB treatment outcomes by diabetes status. There are thus substantial research and policy gaps, particularly with regard to prevention of TB disease in people with diabetes and management of patients with TB–diabetes, both during TB treatment and after successful completion of TB treatment, when they likely remain at high risk of TB recurrence, mortality from TB and cardiovascular disease. Potential strategies to prevent development of TB disease might include targeted vaccination programmes, screening for LTBI and preventive therapy among diabetes patients or, perhaps ideally, improved diabetes management and prevention. The cost-effectiveness of each of these, and in particular how each strategy might compare with targeted TB prevention among other population groups at higher risk of developing TB disease, is also unknown. Despite research gaps, clinicians urgently need practical management advice and more research evidence on the choice and dose of different anti-diabetes medication and effective medical therapies to reduce cardiovascular risks (statins, anti-hypertensives and aspirin). Substantial health system strengthening and integration may be needed to prevent these at risk patients being lost to care at the end of TB treatment.